Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Keywords: freedom; freedom in a complex society

Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Keywords: Marxism; fictitious commodities; imperialism; money

Introduction: Karl Polanyi in the twenty-first century - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
This introduction places the contributions that follow in the context of Polanyi’s rising influence, its causes and effects, and of the key twenty-first century developments that make his oeuvre more relevant than ever. It emphasizes how the contributions push the boundaries of received understandings of Polanyi. While some contributions fill gaping holes, such as those on money as a fictitious commodity, others overturn received understandings, whether that of the double movement or fictitious commodities, or the provenance (Central European or American) of his principal ideas and concerns or how he understood socialism. Yet others demonstrate how amenable Polanyi’s ideas are to further development. Last but not least, the introduction outlines Polanyi’s historical diagnosis as it emerges from these innovative contributions and argues that the stark choice he felt faced European societies, socialism or fascism, is once again before us as we face the groundswell of nationalist and far right forces.
Keywords: capitalism; contemporary relevance; fascism; socialism

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail

Debt, land and money: From Polanyi to the new economic archaeology - Hudson, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
Polanyi spoke of the commodification of money, and this chapter focuses on how interest-bearing debt became the major dynamic, also contributing to the commodification of land and labor. By the late third millennium BC the main way to obtain manual labor was to lend money and make debtors work off their debts as an antichretic interest charge. Personal debt became the lever for creditors to pry land out of the clan-based tenure system, mainly for sale under economic duress. Debtors who pledged their crop or land rights usually ended up forfeiting them. This alienation catalyzed the ‘commodification’ of land. By tracing these debt dynamics, the new economic archaeology is compatible with Polanyi’s intuitions and recognition that market relations are embedded in social relations, and extends his analysis in tracing how administered pricing and monetary valuations created the preconditions for market exchange. The earliest markets, credit and land tenure systems were regulated. Administered pricing was a precondition for creating weights, measures and price equivalencies to enable market exchange to evolve more flexibly.

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.

Polanyi in space - Peck, Jamie (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter addresses the potential of Karl Polanyi’s contribution as a spatial theorist, or as an economic geographer in all but name. Although Polanyi did not identify as a spatial or geographical theorist as such, his work is rich with spatial insights and implications, notably as one of the original analysts of economic diversity. The chapter begins by contextualising Polanyi’s work in relation to the shifting locales and vantage points that shaped its production. It then turns to the question of the potential of Polanyi’s research programme (incomplete as it understandably was) for the conceptualisation and exploration of economic geographies. The goal here is to sketch some of the ways in which neoPolanyian approaches can be put to work in the service of geographically sensitive modes of economic inquiry, including those attuned to the ongoing diversity of economic formations and development trajectories, contemporary engagements with uneven spatial development, and the evaluation of (localised) economic experimentation. Polanyi’s programmatic project of ‘comparative economics’ was never completed during his own lifetime. There is much to be gained from resuming this project.

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Keywords: freedom; reality of society; technology

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.

Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Keywords: Great Transformation, The (Book); double movement; freedom in a complex society; liberal utopia; social facts

Understanding the (Re-)regulation of Private Renting in England: Karl Polanyi, the Rogue Landlord, the Responsible Tenant and the Decent Home - Carr, Helen; Alcock, Rowan (Contract law and the legislature: Autonomy, expectations, and the making of legal doctrine, 2020)

Ecology, democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Duzgun, Eren (Ecology, democracy, and COVID-19, 2020)
This chapter argues that Karl Polanyi’s economic sociology offers foundational concepts for a radical analysis of the social and ecological conditions that have caused the coronavirus pandemic. Furthermore, it shows that Polanyi’s work, often claimed for social democracy, has the potential to provide much more radical insights into the question as to how to “re-embed” our economies, thereby leading to a fundamental rethinking about the ways in which the present crisis can be overcome.
Keywords: COVID-19

The Specter of the 1930s in Asian Nation-Building: Global Fascism, Colonial Biopolitics, and the Origins of Modern Asia - Lee, Alex Taek-Gwang (Back to the ‘30s? : Recurring Crises of Capitalism, Liberalism, and Democracy, 2020)
An analysis of the connection between fascism and biopolitics in modernizing East Asia reveals that fascism served as colonial biopolitics, and was not historically specificity to Europe, though the rise of fascism was central to European colonialism and its technology of governance. As the last stage of capitalism, imperialism came with an expansion of social engineering in colonial countries, forcing colonized peoples to be “civilized.” I challenge the understanding of European fascism, arguing that fascism is inseparable from colonial biopolitics by analyzing non-European experiences in the 1930s. East Asia was then a site in which fascism, premised on building a utopian nation-state, played a pivotal role in encouraging people to insist upon political and economic autonomy in order to compete with Europe. The Manchurian Empire (滿州帝國) was an attempt to realize this utopian idea of fascism. Finally, I argue that these fascist experiences remain influential in the region and constitute a mirror image of European modernity.
Keywords: Japanese Fascism and Imperialism; Japanese colonialism; Manchukuo, history and politics; biopolitics of colonialism; fascism; nationalism and nation-building in East Asia

Where are markets? - Peck, Jamie (Market/Place: Exploring Spaces of Exchange, 2020)
The goal of this chapter is to prepare the ground for theorizing the diversity and spatiality of markets, (necessarily) dealing with, but seeking to move concertedly beyond, the restrictive optic of the orthodox model. It seeks to do so by way of three steps. The following section opens up some preliminary questions about the place of markets and their actually existing historical geography. Next, the chapter turns to the challenge of decentring the market, of moving beyond the idea that the market properly and eternally belongs at the centre of the economic universe. What is the scope for understanding “real markets”, both conceptually and empirically, without recourse to the idealized model of the “pure” market, and all its downstream distortions? Finally, the chapter addresses the question of alternative “mappings” of markets, taking some cues from the work of Karl Polanyi, but urging a more thoroughgoing reconstruction. The chapter’s conclusion acknowledges that the “where?” of markets remains a demanding theoretical question, such that what follows serves to inform some different points of departure, not the destination itself. New answers to this “where?” question, though properly a matter for what Polanyi characterizes as the “substantivist” investigation of real-world market formation, re-formation and transformation, ought to recognize, inter alia: first, the relational character of markets, which are codependent on non-market modes of coordination and regulation; second, their “instituted” form, necessary in function but variable in practice; and not least, third, their always out-of-equilibrium processual dynamics and contradictions.
Keywords: markets; space

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets